PENGARUH IMPLEMENTASI PEMBELAJARAN BERBASIS LESSON STUDY TERHADAP MOTIVASI DAN HASIL BELAJAR INFORMATIKA PADA SISWA SMA PLUS BUDI UTOMO MAKASSAR - M.Ruhan Bachry; Riana T. Mangesa; Jumadi M.parenreng; Djuanda; Abdul Muis Mapalotteng; Ramli Rasyid (UNM Journal of Technology and Vocational, 2022)
The purpose of this study was to obtain, analyze, and describe data regarding (1) Knowing the description of the implementation of collaborative learning based on lesson study in class X SMA Budi Utomo Makassar City (2 Knowing the description of collaborative learning based on lesson study on student learning outcomes in class X SMA Budi Utomo Makassar City 3) Knowing the effect of the implementation of collaborative learning based on lesson study on student learning outcomes in class X SMA Budi Utomo Makassar City. This type of research is quantitative research with True Experiment Design technique. The results of this study show that the implementation of collaborative learning based on lesson study in class X SMA Budi Utomo Makassar City is in the very good category. With a presentation for the Plan stage of 92.3%, the Do stage of 80%, the See stage of 87.5%. the average value with the average value between the experimental class and the control class has a difference, the experimental class with an average value of 73.9 and the control class with an average value of 52.6, with the experimental class being higher than the control class. Meanwhile, the effect of the implementation of collaborative learning based on lesson study on student learning outcomes in class X SMA Budi Utomo Makassar City has a significant effect of 95%. While the effect of the implementation of collaborative learning based on lesson study on students' learning motivation in class X SMA Budi Utomo Makassar City has a significant effect of 95%.